2021
DOI: 10.3389/fpls.2021.716114
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics and Relative Enzymatic Activities Reveal Different Mechanisms in Two Peanut Cultivars (Arachis hypogaea L.) Under Waterlogging Conditions

Abstract: Peanut is an important oil and economic crop in China. The rainy season (April–June) in the downstream Yangtze River in China always leads to waterlogging, which seriously affects plant growth and development. Therefore, understanding the metabolic mechanisms under waterlogging stress is important for future waterlogging tolerance breeding in peanut. In this study, waterlogging treatment was carried out in two different peanut cultivars [Zhonghua 4 (ZH4) and Xianghua08 (XH08)] with different waterlogging toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Another enzyme-apart from GAPDH mentioned above-involved in metabolic adjustment and important for glycolysis is enolase (or phosphopyruvate hydratase). The increase in enolase was reported for flooded tomatoes [14], soybeans [39], and peanuts [31]. These reports and the present study suggest that this glycolytic enzyme might help in intensification of glycolysis for generating energy under hypoxia stress.…”
Section: Global Proteome Analysis After 2xh Candidates For Priming An...supporting
confidence: 79%
See 3 more Smart Citations
“…Another enzyme-apart from GAPDH mentioned above-involved in metabolic adjustment and important for glycolysis is enolase (or phosphopyruvate hydratase). The increase in enolase was reported for flooded tomatoes [14], soybeans [39], and peanuts [31]. These reports and the present study suggest that this glycolytic enzyme might help in intensification of glycolysis for generating energy under hypoxia stress.…”
Section: Global Proteome Analysis After 2xh Candidates For Priming An...supporting
confidence: 79%
“…A greater abundance of ADH protein was noted previously in tomato roots after a one-time waterlogging [14]. For two peanut cultivars, a two-fold higher enzymatic activity for ADH was detected in the roots of the sensitive cultivar than for the tolerant cultivar [31]. After the second hypoxia exposure, adh2 expression in the WL-S accession was similar as for WL-T, which could suggest the adjustment of the sensitive accession and a similar response to that of the tolerant one.…”
Section: Validation Of Selected Proteinsmentioning
confidence: 45%
See 2 more Smart Citations
“…The PPI analysis showed that the interaction between proteins was obvious, and there was a complex network between interacting proteins. The interactions between proteins constitute a major part of the cellular biochemical reaction network, which is of great significance in regulating cells and their signals ( Liu et al, 2021 ). In addition, correlation analysis demonstrated that there existed a weak correlation between the proteome and transcriptome, suggesting that there existed low correlation between transcription level and protein abundance.…”
Section: Discussionmentioning
confidence: 99%